Knowledge, attitude, and practice of endodontists for use of apex locators in clinical practice in India: A survey-based study - Mohd. Irfan Ansari; Vijay Yadav; Sanjay Miglani; Shahnaz Mansoori; Neelam Singh (Wolters Kluwer Medknow Publications, 2024)
Aim: The present study aimed to evaluate the knowledge, attitude, and practice (KAP) of endodontists in India for working length measurements using Apex locators. Methods: This study is an online questionnaire-based survey consisting of 24 questions in total, divided into five parts. The first part consisted of questions related to demographic details, the second part inquires about the tools and technology used for working length determination, and the remaining questions evaluate the KAP regarding the use of apex locators to determine working length (five questions each). Participants in the study were either pursuing or completed postgraduation in endodontics. A total of 257 responses were recorded; however, six participants were excluded due to incomplete submission. Thus, 251 responses were analyzed as descriptive analyses. Correlation analysis and Chi-square tests were performed to find any association between demographic variables and years of experience in practice with KAP of using apex locators by endodontists. Results: In this study, it was observed that the knowledge of the majority of endodontic practitioners was fair, with a positive attitude and practice of using apex locators. Knowledge of the study participants was significantly (P ≤ 0.05) associated with the good attitude and practice of the study participants. Furthermore, years of experience in practice have a positive association with the KAP of endodontists. Conclusion: It can be concluded that endodontists have better clinical acceptance, as they show positive attitudes and practices for using apex locators for working length determination.